Faecal concentrations of progesterone and 17β-oestradiol of female Malayan tapir from different faecal hormone extraction methods - Ruslan, Muhammad Najib; ShikhMaidin, Mashitah; Ramli, Salfarina; Ithnin, Nalisha; Azhar, Intan Nasuha; Mohammed, Nur Hafizah; Zulkifli, Syaizwan Zahmir (Penerbit Universiti Kebangsaan Malaysia, 2022)
Non-invasive hormone monitoring of endangered wildlife provides an essential tool to optimize breeding strategies, mainly in captive management. However, the protocol of reproductive hormone monitoring on pregnancy status using non-invasive faecal samples in Malayan tapir is still inconclusive. Therefore, we compared the metabolites reproductive hormones; 17β-oestradiol and progesterone in the faecal samples extracted using methods of Schwarzenberger et al. (1996) (Methods A and B), Brown et al. (2001) (Method C) and Shutt et al. (2012) (Method D) from pregnant and non-pregnant captive Malayan Tapir. Faecal samples from four female of Malayan Tapir (Tapirus indicus) were collected for five months at Sungai Dusun Wildlife Reserve (n = 2), Zoo Taiping (n = 1) and Zoo Negara (n = 1), Malaysia. Analysis by liquid chromatography-mass spectrometry (LCMS) confirmed that progesterone was detected in all fecal sample extracted by extraction Method A, while 17β-oestradiol was undetectable in all methods. The measurement of reproductive hormones for pregnancy status via Enzyme-Linked Immunosorbent Assay (ELISA) analysis showed no significant difference (p > 0.05) for progesterone between the fecal extraction methods. Yet the data obtained were not able to validate the pregnancy status, due to similarity in concentration for both pregnant and non-pregnant tapirs. While for 17β-oestradiol, significant results were observed in all extraction methods and in pregnancy status (p < 0.05). Method C was found to be the most reliable extraction method (p < 0.05) to indicate pregnancy status. From the results, it showed that solvent used, boiling process and multiphase extraction plays important role in fecal extraction process in Malayan Tapir.